A Survey on Identifying Empathic Expression in Remote Collaboration From Empathic Computing - Prabesh Paudel; Hyung-Jeong Yang; Anjitha Divakaran; Seung-Won Kim; Ji-Eun Shin; Soo Hyung Kim (IEEE Access, 2024)
Empathy has emerged as a valuable tool for communication in today’s digital world, with empathic computing serving as an integral component in facilitating human-like changes such as humanoid robots and fostering comfortable interactions. This article thoroughly explores the realms of empathy, empathic computing, emotion, and their intricate interconnections. Our primary focus is to investigate methods for measuring empathy between two remote collaborators. We review empathy usage and its measurement in remote collaboration and computing process. We analyze recent empathic computing methods in virtual reality and through gaze behavior. Our analysis explores empathy, and the application of empathic computing, and analyze their corresponding responses. We conclude by providing a comprehensive understanding of empathy’s multifaceted nature and its crucial role in establishing mutual understanding and connection between remote agents.